Illuminating the Territorial Principle In Islamic Criminal Law: An in-Depth Investigation Into Enforcing Islamic Penalties for Non-Muslims - Haq, Islamul; Waeduereh, Mustafakama; Suci, Purnama; Resi, Resi (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
This article presents a comprehensive analysis of the Territorial Principle in Islamic Criminal Law, focusing on enforcing Islamic punishments for non-Muslims. The research delves into controversies surrounding the extent to which the jurisdiction of Islamic law is applied in specific regions, particularly concerning the treatment of non-Muslim individuals under the governance of an Islamic state. This literature review will explore reading materials related to the territorial principle and its application in Islamic criminal law concerning non-Muslims. The findings of this research reveal that the theories presented by Imam Abu Hanifah and Abu Yusuf in the Hanafi school of thought offer distinct perspectives on the territorial application of Islamic criminal law. Imam Abu Hanifah asserts that the full implementation of Islamic criminal law is confined to Muslim territories, with punishments applicable to both Muslim and non-Muslim individuals within these boundaries. However, outside these territories, he argues that Islamic law is not obligatory, emphasizing the role of the imam’s authority. Meanwhile, the perspectives of Imam Malik, asy-Syafi’i, and Imam Ahmad propose a universal application of Islamic law, emphasizing the legal subject’s responsibility rather than geographical boundaries, thereby prohibiting Muslims from committing legal violations anywhere